"I'm Glad She Chose Me as Her Parent": Rewards of Caregiving for Adults With Autism. Issue 5 (30th October 2020) - Marsack‐Topolewski, Christina N.; Perry, Tam E.; Chan, Keith T.
Abstract : Objective: This research examines perceptions of rewards associated with caregiving experienced by older parents of adult children with autism spectrum disorder (ASD). Background: More individuals with ASD are reaching adulthood, often requiring some form of lifelong support from parental caregivers. Past research has examined caregiving challenges for adult children with ASD, with little focus on rewards. Method: One‐on‐one, semistructured interviews were conducted among 51 parents (aged 50 years and older) of adult children (18 years and older) diagnosed with ASD. Interviews focused on exploring experiences of older parental caregivers. Using a phenomenological approach, data were coded through a line‐by‐line analysis using Atlas.ti 7 software. Results: Four themes emerged from interview responses: (a) pride in adult child's progress and growth, (b) feelings of personal competence, (c) changed perspective on life, and (d) deeper connections to others. Conclusion: Our findings provide insight into how older parents of adult children with ASD experience rewards from caregiving. Implications: Practitioners who work with individuals with ASD can help parental caregivers and their families find and promote strengths by highlighting the rewards in the caregiving process.